ENGLISH LANGUAGE ANXIETY OF PRE-SERVICE TEACHERS: CAUSES AND COPING STRATEGIES - Pasaribu, Truly Almendo; Harendita, Monica Ella (LLT Journal: A Journal on Language and Language Teaching, 2018)
Teaching practice gives students opportunities to learn from their teaching experience in real schools. However, some may experience anxiety because they lack teaching experience. This feeling can pose potential problems to their learning and teaching process. Although anxiety is not considered a new issue, there has been little information as to how Indonesian pre-service teachersâ experience and overcome anxiety in teaching English as a foreign language. The research aimed at addressing two questions: 1) what are the possible causes of Indonesian pre-service teachersâ anxiety in teaching English? And 2) how do Indonesian pre-service teachers manage anxiety when teaching English? This research employed both quantitative and qualitative methods. The data were collected from questionnaires and focus group discussion. The results show that several factors contributing to pre-service teachersâ anxiety, namely: confidence, English skills, preparation, lesson delivery, studentsâ profiles, evaluation and classroom management. In tackling the problems, the participants applied personal, professional, social, and institutional coping strategies. Recognizing the causes of anxiety and strategies to face it can be one step forward to reduce teaching anxiety.Â DOI:Â doi.org/10.24071/llt.2018.210202Â Â